Effect of Sowing Time, Soil Temperature and Inoculum Density on Suppression of Fusarium Wilt in Lentil (Lens culinaris) - Ghatak, Abhijeet; Shukla, Nandani; Ansar, Mohammad; Balodi, Rekha; Kumar, Jatinder (International Journal of Bio-resource and Stress Management, 2015)
Several questions remain unanswered on escape mechanism of lentil against Fusarium wilt caused by Fusarium oxysporum f. sp.Lentis. Consequently, this study was designed with few parameters including inoculum density, temporal sowing (associated with soil temperature) and its thermal effect with the pathogen. Increased amount of inoculum resulted higher number of diseased plants. However, increased inoculum was proved to be ineffective under cooler condition. Increase in inoculum density numerically enhanced disease incidence at each sowing time (temporal sowing); however, significant difference (p<0.05) increase in disease incidence was detected in the October sown batch. Early sowing associated with high soil temperature (22.6 °C) rendered maximum wilt incidence (97.2%), which is complemented in the laboratory test exhibited by maximum radial growth of the fungus at higher temperature (27 °C). This report suggests development of late sown variety could be a good option to suppress this disease.